TOURISM DEVELOPMENT STRATEGY OF DUCK AND SALTED EGG VILLAGES TO IMPROVE THE COMMUNITY'S ECONOMY - Kartika, Ismi Dwi; Balahmar, Ahmad Riyadh Umar (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to find out the development strategy of Duck and Salted Egg Village Tourism in Kebonsari Village, Candi District, Sidoarjo Regency, as well as how the development can improve the economy of the local community. Kebonsari Village has great potential through duck farming and salted egg production which has become a local identity and educational tourist attraction. Method: qualitative descriptive method with data collection techniques in the form of interviews, observations, and documentation. The analysis was carried out with a theoretical approach to tourism development strategy which includes five indicators, namely accessibility, attractions, amenities, promotion, and institutions, Results: The results of the study show that although this village has quite good access and unique tourist attractions, there are still various obstacles such as lack of supporting facilities, digital promotion that is not optimal, and the absence of official institutions and regulations governing management tour. Novelty : The novelty of this study lies in the focus of development strategies based on local potential and the role of village institutions in building sustainable tourism. This finding can be an input for other villages with similar potential.